Students’ perceptions and challenges in using writing outlines to write an exposition - Radjaban, Yohanes; Humanika, Eko Setyo (Universitas Ahmad Dahlan, 2024)
Problems in developing writing often comes from creative processes in developing ideas to write. Outlines are often recommended as a tool to help students organize their thoughts and structure their writing. This study aims to find out students’ perceptions and the challenges the students encountered when writing an exposition text using provided outlines among the students of English Department of UTY. This study used mixed method approaches. Questionnaires and semi-structured interviews were applied to collect data. Respondents of this study were 20 students (10 males and 10 females) from second year students of English Literature Department of Yogyakarta University of Technology academic year 2023-2024, and through a purposive random sampling technique. A questionnaire was used to figure out students' perceptions, and semi-structured interviews were conducted to find out the challenges encountered by students when writing an exposition text using provided outlines. Nine respondents (6 females and 3 male) were selected in the interview session based on their scores, they were four students with the highest scores, three students with middle scores, and two students with low scores to be interviewed. The semi-structured interview data were analyzed qualitatively using the interactive model. The results of this study show that most students agreed that outlines help them write exposition texts, with 80% agreeing or strongly agreeing with the statement “The outline helps me write an exposition text.” However, students also reported three challenges, difficulty in developing connections between theory and research topics, with 60% indicating they found this aspect challenging, 55% found it challenging to translate their outlines into coherent exposition texts, and 30% students indicated a lack of confidence in their ability to use outlines effectively. This learning model may help students participate, engage, and enhance their confidence in writing exposition texts, and lecturers are aware of the importance of targeted instructional strategies, such as providing more examples and practice opportunities for developing connections between theory and research topics.